Master track of Fridtjof Nansen cruise TIDAL-HX01, 2024-05-16 - 2024-09-18 - Andreas Herber; Verena Meraldi (PANGAEA, 2024)
In addition to the tourist program, a scientific program was carried out on board of the HX vessel M/V Fridtjof Nansen. The measurements onboard took place from May to September 2024 within the framework of "SOOP (Shaping an Ocean Of Possibilities)".